Upregulation of Ferroptosis-Related Fanconi Anemia Group D2 is a Poor Prognostic Factor and an Indicator of Tumor Immune Cell Infiltration in Lung Adenocarcinoma - Zhang, Jingtao; Wang, Dongli; Chen, Xiubao; Ji, Lingyun; Yu, Minmin; Guo, Minghao; Zhang, Dexin; Chen, Weida; Xu, Fei (Frontiers in Genetics, 2022)
Fanconi anemia (FA) group D2 (FANCD2) is a ferroptosis-related gene crucial for DNA damage repair and negatively regulates ferroptosis. Our study aimed to evaluate its prognostic value as well as its association with ferroptosis and immune infiltration in lung adenocarcinoma (LUAD). Transcriptome sequencing data and clinical information, three independent cohorts, as well as immunohistochemistry, were collected from the TCGA, GEO, and HPA databases, respectively. Univariate and multivariate analyses were used to assess the correlations between FANCD2 expression and overall survival or clinicopathological parameters. cBioPortal was utilized to investigate the FANCD2 alteration status. Gene and protein networks based on FANCD2 interactions were generated using GeneMANIA and STRING, respectively. Based on the CancerSEA database, the function of FANCD2 was explored at the single-cell level. The relationships between FANCD2 expression levels and tumor-infiltrating immune cells and their equivalent gene signatures were analyzed by TIMER, GEPIA, TISIDB, and ssGSEA databases. CIBERSORT was used to analyze the relevance of the infiltration of 24 types of immune cells. The results revealed that FANCD2 expression was significantly upregulated in LUAD and lung squamous cell carcinoma (LUSC) tissues than in normal tissues. Further, the overexpression of FANCD2 was closely associated with poor survival for LUAD patients but not for LUSC patients. FANCD2 expression levels were related to tumor-infiltrating immune cells and their matching gene signatures, including CD8+ T cells, natural killer (NK) cells, dendritic (DC) cells, and Th2 cells in cases of LUAD. Therefore, FANCD2 was identified as a crucial molecule underlying the synergistic effects of ferroptosis and immunotherapy for LUAD patients.